2008
DOI: 10.1017/s1742758408004049
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Dicladispa armigera (Coleoptera: Chrysomelidae) haemocytes with Beauveria bassiana

Abstract: Morphology of haemocytes of healthy and Beauveria bassiana (Bals.) Vuill.infected Dicladispa armigera (Olivier) adults was examined in a phase contrast microscope to characterize them into different types. The total haemocyte count (THC) and the differential haemocyte count (DHC) were also estimated. Four types of haemocytes were identified: prohaemocyte, plasmatocyte, granulocyte and spherulocyte. In the healthy adults, the THC varied between 5055 and 5950/mm 3 , out of which 85% were composed of granulocytes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…Our study also observed this phenomenon. At 12 hpi, GR became to accumulate, multipolar filopodial pseudopods elongated, and PL showed a high spreading rate, and these activities determine phagocytosis or early encapsulation 20,55,56 . Effects of host plants on hemocyte morphology were not observed before, but by the scanning electron microscope we found that the percentage of PL‐spreading was the highest and filopodial pseudopods of GR appeared earliest on I. aquatica than the three other diets.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Our study also observed this phenomenon. At 12 hpi, GR became to accumulate, multipolar filopodial pseudopods elongated, and PL showed a high spreading rate, and these activities determine phagocytosis or early encapsulation 20,55,56 . Effects of host plants on hemocyte morphology were not observed before, but by the scanning electron microscope we found that the percentage of PL‐spreading was the highest and filopodial pseudopods of GR appeared earliest on I. aquatica than the three other diets.…”
Section: Discussionmentioning
confidence: 68%
“…Several studies have indicated that entomopathogens can trigger the immune response of herbivores. For instance, Phukan et al 20 . found that Beauveria bassiana infection led to a decrease in the total number of hemocyte cells in beetles.…”
Section: Introductionmentioning
confidence: 99%
“…Giglio et al (2008) observed four morpho-types of haemocytes in the ground beetle Carabus (Chaetocarabus) lefebvrei. Also, four types of haemocytes were identified in the rice hispa beetle Dicladispa armigera: PRs, PLs, GRs and SPs (Phukan et al, 2008). On the other hand, five types of circulating hemocytes were observed in the elm leaf beetle Xanthogaleruca luteola: PRs, PLs, GRs, OEs and SPs (Kohan et al, 2012).…”
Section: Variable Hemocytes In Selected Economic Insectsmentioning
confidence: 99%
“…Sabri and Tariq (2004) determined THC of the red pumpkin beetle Aulacophora foveicollis in 4372 cells/mm 3 . In the healthy adults of the rice hispa beetle Dicladispa armigera, the THC varied between 5055 and 5950cells/mm 3 (Phukan et al, 2008). Jalali and Salehi (2008) recorded the THC in 2 nd instar larvae of P. demoleus as 2008.0cells/mm 3 , in 4 th instar larvae as 9244.0/ mm 3 , in the late prepupae as 12326cells/mm 3 and in newly formed pupae as 6688cells/ mm 3 .…”
Section: Variation Of Total Hemocyte Populationmentioning
confidence: 99%
“…However, information is scarce for Coleoptera for which hemocyte identiÞcation and function have only been reported in a few species of Tenebrionidae Rowley 1979, Zhao andWang 1992), Scarabaeidae (Devauchelle 1971, Brehé -lin and Zachary 1986, Giulianini et al 2003, Cucurlionidae (Manachini et al 2011), Chrysomelidae (Phukan et al 2008), andCarabidae (Giglio et al 2008).…”
mentioning
confidence: 99%